2015
DOI: 10.1051/0004-6361/201525774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gyrochronological and isochronal age estimates for transiting exoplanet host stars

Abstract: Context. Tidal interactions between planets and their host stars are not well understood, but may be an important factor in their formation, structure, and evolution. Previous studies suggest that these tidal interactions may be responsible for discrepancies between the ages of exoplanet host stars estimated using stellar models (isochronal age estimates) and age estimates based on the stars' rotation periods (gyrochronological age estimates). Recent improvements in our understanding of the rotational evolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
96
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 80 publications
(83 reference statements)
18
96
1
Order By: Relevance
“…According to this formula and our measured rotation period, the gyrochronological age of Qatar-2 is 1.4±0.3Gyr. Maxted et al (2015) made an independent estimate of the stellar age by fitting stellar-evolutionary models to the observed spectroscopic parameters and apparent magnitudes. Their result was 15.7±1.4Gyr, significantly older than the gyro age.…”
Section: Stellar Rotation Period and Gyrochronologymentioning
confidence: 99%
“…According to this formula and our measured rotation period, the gyrochronological age of Qatar-2 is 1.4±0.3Gyr. Maxted et al (2015) made an independent estimate of the stellar age by fitting stellar-evolutionary models to the observed spectroscopic parameters and apparent magnitudes. Their result was 15.7±1.4Gyr, significantly older than the gyro age.…”
Section: Stellar Rotation Period and Gyrochronologymentioning
confidence: 99%
“…From these panels it is clear the role that both the chemical composition and the physics inside the models are playing. Maxted et al (2015b) concluded that the gyro-ages are significantly younger than isochrone ages for half of their sample. Second order effect might be at play (magnetism, tidal interactions or other), but until we completely understand all sides of stellar evolution, ages would, somehow, remain elusive.…”
Section: Gyrochronologymentioning
confidence: 91%
“…Maxted et al (2015a) have used a Bayesian approach in order to derive ages based on fits with theoretical models (3.1). They have also derived ages based on gyrochronology (subsection 3.6.1 and Maxted et al 2015b). Figure 24 comes from Maxted et al (2015b), with a caption stating: "Change in the best-fitting masses and ages of transiting exoplanet host stars due to a change in the assumed helium abundance or mixing length parameter.…”
Section: Gyrochronologymentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on a sample of about 25 transiting systems with published V rot sin i or P rot estimates available at that time. Maxted et al (2015) used Bayesian techniques to compare the age estimates from stellar model isochrones to gyrochronological age estimates for 28 transiting exoplanet host stars with accurate mass and radius estimates and directly measured rotation periods. The gyrochronological age estimate was significantly lower than the isochronal age estimate for about half of the stars in that sample.…”
Section: Wide Area Surveys and Hot Jupitersmentioning
confidence: 99%